Exploring our solar system - Tartan, James; Giroux, Donald; Bronson Films; AIMS Media (Chatsworth, CA : AIMS Multimedia, 1995)
Discusses the sun, the planets, asteroids, comets, and meteors in detail, as well as theories on the origins of the solar system, life on other planets, and the existence of other solar systems
Title from title screen
Editor, Susan Heick ; technical advisors, Jeff Cuzzi, Gerald Garner, James Fournier
WINDOWS and MAC requirements not stated. Disc can be used on both systems
Keywords: Solar system -- Software -- Interactive multimedia; Cosmology -- Software -- Interactive multimedia